Pregnane steroids from the twigs and leaves of Strophanthus divaricatus and their cytotoxic activities. (16th March 2022) - An, Pei-Pei; Cui, Yong-Sheng; Shi, Qiong-Yu; Ren, Yu-Hao; Wu, Pei-Qian; Liu, Qun-Fang; Liu, Hong-Chun; Zhou, Bin; Yue, Jian-Min
Graphical abstract: Abstract: Four new pregnanes (1 –4 ), including one 21-norpregnane (4 ), together with two known pregnanes (5 and 6 ), were isolated from the twigs and leaves of Strophanthus divaricatus. Their structures were elucidated on the basis of spectroscopic data analysis, ECD data, and X-ray crystallographic study. The cytotoxic activities of these pregnanes against two human cancer cell lines were evaluated.